Pendidikan Kewarganegaraan Sebagai Upaya Membangun Karakter Kebangsaan di Era Globalisasi - Putri, Mas Fierna Janvierna Lusie; Mumung, Kornelia Efriana; Sulistiawati, Denti (Academy of Social Science and Global Citizenship Journal, 2024)
Citizenship education in the era of globalization plays a very important role in forming national character. Lack of understanding regarding Citizenship Education causes the erosion of national character in the souls of people, especially the younger generation (students and university students). Indonesia's character crisis threatens the value of dignified national character. To resolve the problem of the declining character of the Indonesian nation, especially in the current era of globalization, treatment is needed. This research aims to provide an overview of how important Citizenship Education is in life as a shaper of national character in the era of globalization. Character education also functions to foster potential, habits and behavior, instill a sense of responsibility and leadership, and create abilities and a school environment. Civic education has functions including building participatory skills that make Indonesian citizens active, critical, intelligent and democratic, as well as building a civilized democratic culture. The results of the research show that Citizenship Education as the formation of national character in the era of globalization plays an important role, because as a result of globalization it results in the fading of national character.